Frequência dos fatores de risco cardiovascular nos pacientes acromegálicos com doença controlada e descontrolada - Simone Magnavita Sabino (2009)
Although rare, acromegaly is a disease that has been associated with a 2- to 4- fold increased mortality risk compared to population with the same age and sex. This risk is reduced when patients achieve disease control. Furthermore, the excess of death has been mainly from cardiovascular causes and many studies have already showed increased cardiovascular risk factors in these patients compared to healthy people. There is a lot of controversy about many issues in acromegaly as the best GH cut off level for disease control. Besides these facts, recent progress has been made and special emphasis has been given to genetic and molecular aspects in acromegaly. All these issues motivated the articles presented in this dissertation. The first article tested the hypothesis that there should be a higher frequency of cardiovascular risk factors and metabolic syndrome in uncontrolled acromegalic patients compared to controlled ones. For this purpose, sixty-eight acromegalic patients were selected from outpatients of the Neuroendocrinololy unit of School of Medicine of Federal University of Minas Gerais, Santa Casa of Belo Horizonte and private offices in Belo Horizonte. Patient assessments were performed from December 2006 to December 2008. After an overnight fast, a peripheral venous blood sample was obtained for the measurement of the following variables: basal GH and IGF-1 levels, lipid profile (total cholesterol, HDL cholesterol, very-low-density lipoprotein - VLDL cholesterol, LDL cholesterol, and triglycerides), plasma glucose and insulin levels. Anthropometric measures (BMI and waist circunference) and blood pressure measurements were performed in all study subjects by the same person. Smoking habit and medications in use were assessed. According to GH and IGF-1 levels, patients were allocated in two groups: controlled disease (basal GH < 2.0g/L and IGF-1 in the normal range for age) and uncontrolled disease (basal GH 2.0g/L or IGF-1 above the normal range for age). Frequency of hypertension, diabetes mellitus, dyslipidemia, metabolic syndrome and altered homeostasis model assessment of insulin-resistance HOMA IR, BMI and waist circumference were assessed in the two groups. Thirty-three patients (48.52%) had their disease controlled while 35 patients (51.47%) had uncontrolled acromegaly despite having been treated. After univariate analysis, there was no difference in frequency of cardiovascular risk factors and metabolic syndrome between the two groups. After multivariate analysis, GH and IGF-1 correlated inversely with LDL-cholesterol (p = 0.012 and p = 0.006 respectively) and HOMA IR correlated directly with IGF-1 (p = 0.018). GH was also inversely correlated with waist circunference (OR = 9.6, CI = 1.1 87.1, p = 0.044). GH cut off levels of 1.0g/L and 2.5g/L for disease control criteria were also tested but they both showed low sensitivity in predicting the cardiovascular risk factors evaluated and metabolic syndrome. A ROC curve was designed in order to estimate which GH cut off level would show better sensitivity in detecting the presence of each variable evaluated. The GH values ranged between 0.07 and 0.38g/L, which were very low. We concluded that, with current GH cut off levels for disease control, there was no difference in the frequency of cardiovascular risk factors and metabolic syndrome between controlled and uncontrolled disease groups. The second paper was a review article where we attempted to address the genetic and molecular aspects regarding acromegaly´s presentation and therapeutics. In this article, we assessed the mutations related to familial and non familial somatotropinomas and also the recent discoveries interfering in the results of treatments.